Hume and Mandeville on Division of Labour, or, the World of Invention - Pedro Paulo Pimenta (Revista de Filosofia Moderna e Contemporânea, 2022)
This article proposes approximations between Hume and Mandeville based on the way each of them understands the division of labour as a modern phenomenon characteristic of European commercial societies. The starting point, common to both, is the idea that man, or human nature, is an animal moved by passions that are very similar, if not identical, to those of other animals, notably mammals. The anthropology underlying the division of labour thus has a physiological root. The same paradox interests these authors: the process of the division of labour, which enables the production of so many excellent artefacts, is the labour of unqualified artisans. There is, therefore, a disparity between the product and the principle that engenders it. As we intend to show, this is the leitmotiv of a critique, addressed by Hume, of the teleological proofs of the existence of God.